2019
DOI: 10.1111/apa.14954
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implants before 9 months of age led to more natural spoken language development without increased surgical risks

Abstract: The importance that early auditory stimulation has on the infant's plastic brain with regard to optimal listening and language development is well-known. 1,2 During the first year of life, infants with normal hearing start to pay attention to the acoustic features of the speech they are surrounded by. They also develop phonology and acquire the statistical patterns that are important for word segmentation. 3 Children with congenital hearing loss are now identified earlier because of universal hearing screening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 29 publications
4
65
1
4
Order By: Relevance
“…When providing children with amplification devices such as HAs or CIs, the goal is to allow the development of spoken language skills that are close to, or equivalent to, their peers who do not have hearing loss. Even though numerous studies suggest earlier diagnosis and access to amplification is associated with better outcomes (Carew et al, 2018;Ching, 2015;Ching et al, 2013;Cupples et al, 2018;Dettman et al, 2016;Forli et al, 2011;Geers, Moog, Biedenstein, Brenner, & Hayes, 2009;Karltorp et al, 2019;Leigh et al, 2013;Manrique et al, 2004;Miyamoto et al, 1999;Sininger et al, 2010;Svirsky et al, 2004;Wie, 2010), many studies still indicate that children with hearing loss do not have language outcomes that are as good as their peers. The estimated delays vary, but several studies report group-average language levels of approximately 1-2 standard deviations below the normative mean, based on one or more measures (see e.g.…”
Section: Language Outcomes In Children With Hearing Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…When providing children with amplification devices such as HAs or CIs, the goal is to allow the development of spoken language skills that are close to, or equivalent to, their peers who do not have hearing loss. Even though numerous studies suggest earlier diagnosis and access to amplification is associated with better outcomes (Carew et al, 2018;Ching, 2015;Ching et al, 2013;Cupples et al, 2018;Dettman et al, 2016;Forli et al, 2011;Geers, Moog, Biedenstein, Brenner, & Hayes, 2009;Karltorp et al, 2019;Leigh et al, 2013;Manrique et al, 2004;Miyamoto et al, 1999;Sininger et al, 2010;Svirsky et al, 2004;Wie, 2010), many studies still indicate that children with hearing loss do not have language outcomes that are as good as their peers. The estimated delays vary, but several studies report group-average language levels of approximately 1-2 standard deviations below the normative mean, based on one or more measures (see e.g.…”
Section: Language Outcomes In Children With Hearing Lossmentioning
confidence: 99%
“…However, what exactly is meant by "earlier" varies. Some find better outcomes if children are implanted before three years old (Manrique, Cervera-Paz, Huarte, & Molina, 2004;Miyamoto, Svirsky, Kirk, & Sehgal, 1999) before two years old (Svirsky, Teoh, & Neuburger, 2004), before 12 months (Ching et al, 2013;Dettman et al, 2016;Forli et al, 2011;Leigh, Dettman, Dowell, & Briggs, 2013;Wie, 2010), and yet others recommend implantation before 9 months (Karltorp et al, 2019). The lack of correlation between age at implantation and later language skills in some studies may be due to low degrees of variability in age at implantation among those studied.…”
Section: Introduction Of Sound For Auditory Developmentmentioning
confidence: 99%
“…As the implantation age is younger, the development of language is closer to that of children with normal hearing. In a study, Karltorp et al showed that 4 years after implantation, children implanted until the age of 9 months had a language development similar to a normal-hearing child of the same age, while children implanted between 18 and 29 months old had delayed development of language [ 35 ]. In a study by Colletti et al on a sample of 10 children who had been implanted before the age of 1, the authors showed that babbling appeared after 1–3 months after the implant activation [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…A delay in ToM might lead to additional problems. Previous studies have shown that some children with CIs are delayed in terms of their ToM (Ketelaar et al, 2012;Liu et al, 2018), especially those that receive their CI late (Sundqvist et al, 2014). Further, both Most et al (2010) and Jeanes et al (2000) argue that less possibility to practice pragmatic language skills might lead to a delayed development in children with CIs.…”
Section: Pragmatic Language Abilitymentioning
confidence: 99%